2019
DOI: 10.1038/s41598-019-50166-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD44 intracellular domain production suppresses bovine articular chondrocyte de-differentiation induced by excessive mechanical stress loading

Abstract: CD44 fragmentation is enhanced in chondrocytes of osteoarthritis (OA) patients. We hypothesized that mechanical stress-induced enhancement of CD44-intracellular domain (CD44-ICD) production plays an important role in the de-differentiation of chondrocytes and OA. This study aimed to assess the relationship between CD44-ICD and chondrocyte gene expression. Monolayer cultured primary bovine articular chondrocytes (BACs) were subjected to cyclic tensile strain (CTS) loading. ADAM10 inhibitor (GI254023X) and γ-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In experiments using primary cells, bovine articular chondrocytes (BACs) were isolated from full thickness slices of the articular surface of metacarpophalangeal joints of young adult steers (aged 18-24 months), which were provided by Nagoya City Central Wholesale Market. These slices were digested in 0.2% (0.05 g) pronase (catalogue number: 537088, activity: ≥70,000 proteolytic units/g dry weight, Merck, Germany) for 1 hour at 37 °C and subsequently in 0.025% (0.00625 g) collagenase P (catalogue number: 11213865001, activity: >1.5 U/mg lyophilizate, Roche, Germany) overnight at 37 °C 4,29 . Cells were cultured in DMEM/Ham's F12 medium with 1 × insulin-transferrin-sodium selenite (ITS), 4% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin, and 0.25 μg/ml amphotericin at 37 °C in a 5% CO 2 environment.…”
Section: Methodsmentioning
confidence: 99%
“…In experiments using primary cells, bovine articular chondrocytes (BACs) were isolated from full thickness slices of the articular surface of metacarpophalangeal joints of young adult steers (aged 18-24 months), which were provided by Nagoya City Central Wholesale Market. These slices were digested in 0.2% (0.05 g) pronase (catalogue number: 537088, activity: ≥70,000 proteolytic units/g dry weight, Merck, Germany) for 1 hour at 37 °C and subsequently in 0.025% (0.00625 g) collagenase P (catalogue number: 11213865001, activity: >1.5 U/mg lyophilizate, Roche, Germany) overnight at 37 °C 4,29 . Cells were cultured in DMEM/Ham's F12 medium with 1 × insulin-transferrin-sodium selenite (ITS), 4% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin, and 0.25 μg/ml amphotericin at 37 °C in a 5% CO 2 environment.…”
Section: Methodsmentioning
confidence: 99%
“…CD44 also targets the canonical Wnt/ β -catenin pathway and the EMT process [ 124 , 125 ]. The increase in ICD diminishes Sox9 expression in articular chondrocytes thus diminishing the expression of genes associated to differentiation and favoring the expression of genes associated to stemness [ 126 ]. ICD also binds to CREB, and the dimer binds to PFKB4, a promoter that activates glycolysis and stemness in breast cancer cells [ 80 ], whereas in thyroid cancer cells, it facilitates the recruitment of cyclin D1 and thus cell proliferation [ 81 ].…”
Section: Main Textmentioning
confidence: 99%
“…Sobue et al. confirmed demonstrated that excessive mechanical stress loading induces the de-differentiation of articular chondrocytes via CD44 cleavage and subsequent CD44- intracytoplasmic domain production, suggesting CD44 as a potential therapeutic target [ 96 ]. A more recent study revealed that excessive mechanical stress led to increased activities of integrins α V β 3 and α V β 5 in chondrocytes and up-regulated gene expression of IL-1β, TNF-α, MMP-3, and MMP-13 through phosphorylation of FAK and MAPKs [ 97 ].…”
Section: The Challenges Of Articular Cartilage Regeneration In Obesitmentioning
confidence: 99%
“…Additionally, Leong and colleagues observed that moderate (2.5 ​MPa, 1 ​Hz) levels of IHP suppresses basal MMP-1 expression and up-regulates ED-rich tail 2 (a mechanosensitive transcriptional coregulator), whereases high IHP (10 ​MPa) caused a profound increase in CITED2 and a decrease in MMP-1 mRNA expression in rat articular cartilage explants [ 128 ]. In obese individuals, mechanical overloading significantly decreased the mRNA expression of SOX9, aggrecan, and COL2A but increased COL1 mRNA expression in bovine articular chondrocyte by enhancing CD44 cleavage, thus inhibiting chondrogenic differentiation [ 96 ]. Together, these findings illustrate that understanding how stem cells respond to the hostile disease microenvironment will be central to realising the potential of stem cell-based therapies for articular cartilage repair.…”
Section: The Challenges Of Articular Cartilage Regeneration In Obesitmentioning
confidence: 99%